Bulk growth, structural, vibrational, crystalline perfection, optical and dielectric properties of L-threonine doped KDP single crystals grown by Sankaranarayanan-Ramasamy (SR) method. (23rd February 2017) - Shkir, Mohd.; Ganesh, V.; AlFaify, S.; Algarni, H.; Bhagavannarayana, G.; Maurya, K. K.; Abutalib, M. M.; Yahia, I. S.
Abstract : In the present work, the authors have grown the bulk-sized single crystals of pure (Size ~ 45 × 10 × 10 mm 3 ) and first time L-threonine (LT)-doped (Size ~ 85 × 10 × 8 mm 3 ) KDP with high quality by Sankaranarayana-Ramasamy (SR) method in an aqueous solution at constant temperature. A remarkable enhancement in the growth rate was observed from 3.2 mm/day (pure) to 6 mm/day (LT doped), respectively. The crystal structure, lattice parameters and growth direction were confirmed by powder X-ray diffraction analysis. FT-IR study confirms the presence of L-Threonine doping in KDP. Further, the vibrational modes and surface morphology was studied by FT-Raman spectroscopy along with etching treatment and shows remarkable reduction of surface defects. The optical transparency of SR-grown KDP crystals was found to be enhanced from 76 to 88% due to LT doping. The optical band gap was calculated for both the crystals and found to be 5.68 and 5.53 eV. Crystalline perfection of the grown crystals was assessed by high-resolution X-ray diffraction, dielectric and wet chemical etching studies and found to be good. The obtained result shows that the grown crystals can be used for laser applications.